Dystopian Themes in Brave New World and The Hunger Games: A Comparison - Müllerová, Bára (Univerzita Pardubice, 2020)
In this master's thesis, two dystopian novels, Brave New World and The Hunger Games (referring only to the first volume of the series), are analyzed as individually standing products of the same literary stream which in their own ways adhere to the themes, motifs, and clichés typical for the genre. Subsequently, the two pieces are juxtaposed in terms of similarities as well as differences in order to assess the constancy of the dystopian genre regardless of the time period or the distinct historical and cultural context contributing to the creation of such novels. The intermission between the release of the former book (Brave New World) and the latter book (The Hunger Games) spanning almost 80 years, the two works offer a debilitating insight into oppressive cultures that present themselves as utopian despite being strongly dystopian and laying their foundations on the repression and exploitation of the lower classes. Taking into consideration this initial resemblance of the focal topic which each of the authors chose as the primary and defining point of their respective books, this thesis attempts to trace further parallels between the two pieces when breaking them into smaller categories such as main themes, character archetypes, and the overall message of the storyline. Simultaneously with this effort, however, this paper also aspires to locate and explain any differences emerging in the same aforementioned categories (themes, archetypes, metaphors). That is done by examining how historical context may have shaped the authors' personal (yet culturally motivated) outlook on the dystopian genre in terms of how to portray an oppressed society. The thesis is divided into three major parts and the juxtaposition itself. Firstly, an insight into the history of dystopia as a literary genre is provided in detail, focusing on its metamorphosis from utopia into antiutopia and, finally, into dystopia as the contemporary reader knows it, all the while establishing that the selected novels do indeed belong to this vast category of literature. Secondly, dystopia is examined more closely through its typical themes, archetypes etc., using the two selected novels as a vivid illustration of these factors in practice. Thirdly, historical context preceding and accompanying the origins of the books is offered in order to classify them as products of their own individual cultures (British and American, respectively), delineating  possible reasons for the authors' varying approaches when creating and describing a dystopian world and its society. And lastly, the two novels are put side by side and contrasted in regards to the central motifs employed by each of the authors, concentrating on drawing comparisons as well as distinctions between the two pieces. As such, this paper strives to demonstrate that even two authors of different epochs and cultures can write corresponding works; not because they would respond to the same situation, but in spite of the fact they react to different times and problems and create completely unique worlds and works.
Porovnání dystopických témat v dílech Brave New World a The Hunger Games
Keywords: dystopie; utopie; dobový kontext; porovnání; Brave New World; Hunger Games; dystopia; utopia; historical context; juxtaposition; Brave New World; Hunger Games